Le On - Off. - Désanges, Guillaume; Josse, Béatrice; Lunghi, Enrico; Melcher, Ralph; Rousseau, Pascal (Luxembourg : Casino Luxembourg - Forum d'Art Contemporain Luxembourg, 2006)
Bourgeat, Lilian ; Chang, Fei Hsia ; Charlier, Jacques ; Claerbout, David ; Cordes, Christian H. ; Decker, Simone ; Diaz Morales, Sebastián ; Dumont, Jean-Jacques ; Duras, Marguerite ; Floyer, Ceal ; Hausig, Daniel ; Höller, Carsten ; Holzer, Jenny ; Janssens, Ann Veronica ; Kogler, Peter ; Kuball, Mischa ; Kubisch, Christina ; Low, Antonia ; McCall, Anthony ; McQueen, Steve ; Oursler, Tony ; Petitgand, Dominique ; Rehberger, Tobias ; Rondepierre, Eric ; Schnell, Ruth ; Sester, Marie ; Stratmann, Veit ; Verjux, Michel
On - Off, Casino Luxembourg - Forum d'Art Contemporain Luxembourg, 2006-12-09. 2007-02-25
boek